The Effect of a 100-km Ultra-Marathon under Freezing Conditions on Selected Immunological and Hematological Parameters - Žákovská, Alena; Knechtle, Beat; Chlíbková, Daniela; Miličková, Marie; Rosemann, Thomas; Nikolaidis, Pantelis T. (Frontiers in Physiology, 2017)
Although moderate exercise is beneficial for the human body and its immune system, exhaustive ultra-endurance performance in cold conditions might be harmful. The aim of this study was to examine the effect of a 100-km ultra-marathon under cold conditions (temperatures from -1°C to +1°C) on selected immunological, biochemical and haematological parameters. Participants were 15 runners (12 men and three women, age 40.3±9.7 years, body mass 67.3±9.0 kg and body height 1.74±0.10 m, mean±standard deviation). Leukocytes increased (p<0.01) and, particularly, the number of leucocytes doubled in seven out of 15 athletes. Immature neutrophils, mature neutrophils and monocytes increased (p<0.02), whereas lymphocytes and eosinophils did not change. IgG increased (p<0.02), but IgA and IgM remained unchanged. Platelets increased (p<0.01), whereas red blood cells, hematocrit and haemoglobin did not change. LDH (lactate dehydrogenase) and CK (creatine kinase) increased (p<0.01), but ALT (alanine aminotransferase) did not change. There was an association between the markers of the acute inflammation of the organism (i.e. neutrophils, immature neutrophils, platelets and monocytes) and the markers of muscle damage (i.e. CK, platelets and LDH). There were no relationships among all the markers in relation to upper respiratory tract infections and liver damage. The highest change was noted in the increase of the number of immature neutrophils (1019.2%) and CK levels (1077.6%). In summary, this is the first study investigating immunological, haematological and biochemical parameters and showing that running a 100-km ultra-marathon under cold conditions leads to changes in several immunological, biochemical and haematological parameters indicating a severe stress on the body associated with increasing susceptibility to the development of infections.